Miskonsepsi Siswa dalam Menyelesaikan Masalah Matematika Ditinjau dari Gaya Berpikir Gregorc - Mega Arofatul Jannah; Afifah Nur Aini (JUMAT: Jurnal Matematika, 2024)
One of the reasons for the low mathematical problem-solving ability is students’ misconceptions. Therefore, it is important to identify it. Misconceptions are defined as misunderstandings of concepts due to initial understanding or errors in linking between concepts. Misconceptions can be influenced by thinking style. Thinking style is a way of organizing and managing the information obtained. Gregorc classifies thinking styles into Concrete Sequential, Abstract Sequential, Concrete Random, and Abstract Random. This research aims to identify student misconceptions in terms of thinking style and held in the odd semester of the 2022/2023 academic year. The research was qualitative and descriptive, with 21 students in class VIII A of SMP Negeri 3 Rambipuji. The instruments used were a thinking-style questionnaire, diagnostic test, and interview guide. At the initial stage, a questionnaire was given to determine their thinking style. Then each student was selected to take the test. The test results are analyzed based on misconception indicators. Data were analyzed referring to Miles and Huberman's stages: data reduction, data presentation, and conclusion. The research results showed that students with Concrete Sequential, Concrete Random, and Abstract Random thinking styles experienced all three types of misconceptions, while Abstract Sequential only experienced classificational and theoretical misconceptions.